Phenylphosphonic Acid on Rutile TiO2(110): Using Theoretically Predicted O 1s Spectra to Identify the Adsorption Binding Modes - Wolfram, Alexander; Muth, Maximilian; Köbl, Julia; Mölkner, Andreas; Mehl, Sascha; Tsud, Nataliya; Steinrück, Hans-Peter; Meyer, Bernd; Lytken, Ole (Journal of Physical Chemistry C, 2024)
We have studied the adsorption of phenylphosphonic acid on rutile TiO2(110)-(1 × 1) using high-resolution synchrotron-radiation photoelectron spectroscopy and near-edge X-ray absorption fine-structure spectroscopy (NEXAFS). Upon adsorption at room temperature, we observe a complex O 1s spectrum, a single P 2p multiplet and the disappearance of small polarons in the Ti 2p and valence-band regions. Upon heating to 450-500 K, the O 1s spectrum changes, an additional P 2p species appears, the polaron signals reappear even stronger and NEXAFS indicates a more flat-lying molecule. Using density functional theory (DFT), we have determined the most stable adsorption configurations on the surface. For these configurations, we have calculated the O 1s and P 2p binding-energy positions of all oxygen and phosphorus atoms, including the first three trilayers of the TiO2(110) substrate. In addition, we have used the orientations of the phenyl rings from the DFT structures to calculate the expected polar and azimuthal angular dependencies in carbon K-edge NEXAFS. This allows us to compare our calculated adsorption configurations with the experimental observations. Below 450 K, we find a singly deprotonated bidentate species to be in perfect agreement with the experimental data. Above 500 K, the desorption of water creates oxygen vacancies, and we find a mixed bidentate and rotated-tridentate adsorption structure to be in good agreement with the experimental observations.
CRIS-Team Scopus Importer:2024-07-26